PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PENGUKURAN LUAS PESERTA DIDIK KELAS IV SDN 05 AIR TAWAR BARAT - Ramadhani Safitri Azwal; Yarisda Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics learning is expected to train students’ thinking patterns so they develop the ability to solve problems. However, mathematics is often considered difficult and disliked by students because teachers rarely use models or media that can help attract students’ interest in learning, resulting in students having difficulty understanding the material. This study aims to determine the effect of the Problem Based Learning (PBL) model on the learning outcomes of area measurement for fourth-grade students at SDN 05 Air Tawar Barat. This research is quantitative, using an experimental approach with a quasi-experimental design in the form of a Nonequivalent Control Group Design. Sample data was collected using purposive sampling, with the population consisting of fourth-grade students from public elementary schools in Region III, Padang District. The selected samples were class IV A of SDN 05 Air Tawar Barat as the experimental class and class IV B of SDN 05 Air Tawar Barat as the control class. The instrument used in this study was an objective test in the form of multiple-choice questions. Based on the research results, the average post-test score of the experimental class was 63.39, while the control class scored 50.32. The t-test showed a significance value of 0.002 < 0.05, and the calculated t-value was 3.183 > 2.00488. Therefore, according to the decision rule for the Independent Sample T-Test, H₀ is rejected and Hₐ is accepted, indicating a significant effect of using the Problem Based Learning model on the learning outcomes of area measurement for fourth-grade elementary school students.These findings are consistent with broader research showing that PBL enhances students’ mathematics learning outcomes, problem-solving abilities, and engagement compared to conventional methods